Molten salt auxiliary valence gradient doped modified single crystal positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202411219587.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
[0004]本发明的目的在于提供一种熔盐辅助价态梯度掺杂改性单晶正极材料及其制备方法与应用,解决传统未经改性的尖晶石LiMn2O4正极材料产生Mn3+的Jahn-Taller畸变、Mn3+歧化反应等现象进而导致容量衰减的问题
[0020] (1) The present invention uses molten salt to assist the doping of transition metal elements into the lithium manganate cathode material. The molten salt can provide a molten liquid environment during the sintering process, allowing the transition metal doping elements to be evenly distributed inside the material. In subsequent processing The medium molten salt can be completely removed by washing, and single crystal materials modified by gradient doping with different valence states are finally synthesized. If the molten salt is not removed, pure lithium manganate materials cannot be synthesized, and the final product contains impurity phases. The process of removing molten salt will cause defects on the material surface. Tempering can repair the surface structure of the material and remove excess moisture.
Smart Images

Figure CN119121372A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a molten salt-assisted valence gradient doped modified single crystal positive electrode material and a preparation method and application thereof. Background Art
[0002] Over-reliance on fossil energy production and consumption has long led to inconsistency and insecurity between energy and the environment, which has become a common problem faced by countries around the world. As the global energy system based on fossil energy is increasingly concerned about energy depletion and environmental pollution, people have an urgent need for renewable clean energy and the energy conversion and storage systems that are compatible with it.
[0003] Rechargeable lithium-ion batteries (LIBs) have the advantages of high output voltage, good safety performance, and long cycle life. They have become an important energy supply device for portable electronic products, electric vehicles, and even large-scale energy storage systems. However, there are certain obstacles to the development of LIBs, such as the structural stability of the positive electrode material and surface side reactions. Among them, spinel LiMn2O4 positive electrode materials have attracted much attention due to their advantages such as stable skeleton, three-dimensional diffusion channels of Li, low Coulomb repulsion and good thermal stability, as well as the outstanding advantages of abundant reserves of Mn elements, non-toxicity, and environmental protection. Although the spinel structure has obvious advantages, the capacity decay of LiMn2O4 is a fatal flaw. In particular, LiMn2O4 will produce the following changes in high temperature environments: (1) During deep discharge, Mn 3+ Jahn-Taller distortion; (2) Mn 3+ Disproportionation reaction (Mn 3+ →Mn 4+ +Mn 2+ ) will lead to the dissolution loss of manganese. The large dissolution loss of active manganese ions will lead to an irreversible decrease in specific capacity; (3) the decomposition of the electrolyte produces HF, which corrodes the electrode; (4) oxygen defects caused by the material synthesis process and / or electrolyte decomposition; (5) irreversible phase changes trigger the formation of microcracks; (6) the deposition of manganese on the negative electrode leads to the destruction of the electrolyte interface (SEI) and the increase of impedance. Summary of the invention
[0004] The purpose of the present invention is to provide a molten salt assisted valence gradient doping modified single crystal positive electrode material and its preparation method and application, so as to solve the problem of Mn generation in the traditional unmodified spinel LiMn2O4 positive electrode material. 3+ Jahn-Taller distortion, Mn 3 + Disproportionation reactions and other phenomena lead to capacity decay.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a molten salt-assisted valence gradient doping modified single crystal positive electrode material, comprising the following steps:
[0007] (1) mixing a transition metal source, a lithium source, a manganese source and a molten salt additive, sequentially performing a first sintering and a second sintering, removing the molten salt additive, and obtaining a doped and modified single crystal positive electrode material precursor;
[0008] (2) subjecting the doped modified single crystal positive electrode material precursor to a tempering treatment to obtain a molten salt assisted valence gradient doped modified single crystal positive electrode material;
[0009] Wherein, the transition metal source in step (1) is Mg 2+ 、Sm 3+ 、Ti 4+ , Nb 5+ with Mo 6+ A transition metal oxide containing one or more doping elements.
[0010] Preferably, in the preparation method, in step (1), the lithium source includes LiOH·H2O or Li2CO3, the manganese source includes MnCO3, Mn3O4 or MnO2, and the molten salt additive is Li2SO4·H2O.
[0011] Preferably, in the preparation method, in step (1), the molar ratio of the transition metal source, the lithium source, the manganese source and the molten salt additive is 0.01:1-1.08:2:1-2.
[0012] Preferably, in the preparation method, in step (1), the mixing method is ball milling; the ball milling time is 3 to 6 hours, the rotation speed is 300 to 400 r / min, and the ball-to-material ratio is 10 to 20:1.
[0013] Preferably, in the preparation method, in step (1), the temperature of the first sintering is 400-500° C., the time is 3-6 hours, and the rate of heating to the required temperature for the first sintering is 1.5-3° C. / min.
[0014] Preferably, in the preparation method, in step (1), the temperature of the second sintering is 750-850° C., the time is 10-14 hours, and the rate of heating to the temperature required for the second sintering is 1.5-3° C. / min.
[0015] Preferably, in the preparation method, in step (1), the atmosphere of the first sintering and the second sintering is an oxygen atmosphere.
[0016] Preferably, in the preparation method, in step (2), the temperature of the tempering treatment is 700-750°C, the time is 4-6 hours, and the rate of heating to the temperature required for the tempering treatment is 1.5-3°C / min.
[0017] The present invention also provides a molten salt-assisted valence gradient doping modified single crystal positive electrode material prepared by the preparation method.
[0018] The present invention also provides an application of the molten salt-assisted valence gradient doping-modified single crystal positive electrode material in a lithium-ion battery.
[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention uses molten salt to assist transition metal elements in doping into lithium manganese oxide positive electrode materials. The molten salt can provide a molten liquid environment during the sintering process, allowing the transition metal doping elements to be evenly distributed inside the material. In subsequent treatments, the molten salt can be completely removed by washing, and finally a single crystal material modified by doping with different valence gradients is synthesized; if the molten salt is not removed, pure lithium manganese oxide materials cannot be synthesized, and the final product contains impurity phases. In the process of removing the molten salt, defects will be generated on the surface of the material. The tempering treatment can repair the surface structure of the material and remove excess moisture.
[0021] (2) The doped modified single crystal positive electrode material prepared by the present invention can effectively avoid the capacity loss of the material, significantly reduce the lattice mismatch in the process of lithium extraction / insertion, and alleviate the volume strain in the process of charging and discharging. At the same time, the formed MO bond (M refers to transition metal) can enhance the structural stability of the material and inhibit the formation of microcracks in the material. Bulk doping can enhance the structural stability of the material without changing the basic framework of the material, including the adjustment of the bulk and interface structure; secondly, bulk doping can effectively improve the diffusion kinetics of lithium ions, significantly reduce the Li transmission barrier, and improve the ion transport rate. The preparation method of the positive electrode material described in the present invention is applicable to the existing preparation methods of positive electrode materials, such as solid phase method and wet chemical method, which is convenient for industrial application and provides ideas for commercial modified positive electrode materials.
[0022] (3) The cycle stability of the lithium-ion battery prepared using the positive electrode material of the present invention is significantly increased, and the side reactions on the electrode surface are suppressed; moreover, the number of charge and discharge cycles of the obtained battery is significantly improved, and its energy density, safety, reliability, etc. are significantly better than those of unmodified lithium-ion batteries of the same type and model, which is conducive to commercial application.
[0023] (4) The molten salt-assisted valence gradient doping modified single crystal positive electrode material provided by the present invention will not increase the cost of lithium-ion battery preparation, and the production equipment involved is simple, the production cycle is short, the process is simple, and it is suitable for large-scale production.
[0024] (5) The doping modification method of the present invention has wide adaptability and is applicable to lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based positive electrode materials, lithium cobalt oxide, ternary layered materials or lithium iron phosphate positive electrode materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments or the prior art are briefly introduced below.
[0026] Figure 1 Schematic diagram of the preparation process of molten salt-assisted valence gradient doping modified single crystal cathode material;
[0027] Figure 2 XRD diagrams of the positive electrode materials obtained in Examples 1 to 5 and Comparative Example 1;
[0028] Figure 3 The following are the test results of the cycle performance of the batteries obtained in Application Examples 1 to 5 and Comparative Application Example 1. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a molten salt-assisted valence gradient doping modified single crystal positive electrode material, comprising the following steps: Figure 1 As shown:
[0030] (1) mixing a transition metal source, a lithium source, a manganese source and a molten salt additive, sequentially performing a first sintering and a second sintering, removing the molten salt additive, and obtaining a doped and modified single crystal positive electrode material precursor;
[0031] (2) subjecting the doped modified single crystal positive electrode material precursor to a tempering treatment to obtain a molten salt assisted valence gradient doped modified single crystal positive electrode material;
[0032] Wherein, the transition metal source in step (1) is Mg 2+ 、Sm 3+ 、Ti 4+ , Nb 5+ with Mo 6+ A transition metal oxide containing one or more doping elements.
[0033] In the present invention, the transition metal source in step (1) preferably comprises Mg 2+ 、Sm 3+ 、Ti 4+ , Nb 5+ Or Mo 6+ The transition metal oxide doped with an element, preferably comprising Ti 4+ , Nb 5+ Or Mo 6+ A transition metal oxide doped with an element, more preferably comprising Mo 6+Transition metal oxides doped with elements.
[0034] In the present invention, the lithium source in step (1) preferably includes LiOH·H2O or Li2CO3.
[0035] In the present invention, the manganese source in step (1) preferably includes MnCO3, Mn3O4 or MnO2, and further preferably includes MnCO3 or Mn3O4.
[0036] In the present invention, the molten salt additive in step (1) is preferably Li2SO4·H2O.
[0037] In the present invention, the molar ratio of the transition metal source, the lithium source, the manganese source and the molten salt additive in step (1) is preferably 0.01:1-1.08:2:1-2, more preferably 0.01:1.02-1.06:2:1.2-1.6, and more preferably 0.01:1.05:2:1.4.
[0038] In the present invention, the mixing method in step (1) is preferably ball milling.
[0039] In the present invention, the ball milling equipment is preferably a planetary ball mill.
[0040] In the present invention, the ball milling time is preferably 3 to 6 hours, more preferably 4 to 5 hours, and more preferably 4 hours; the rotation speed is preferably 300 to 400 r / min, more preferably 350 to 400 r / min, and more preferably 400 r / min; the ball-to-material ratio is preferably 10 to 20:1, more preferably 10 to 15:1, and more preferably 10:1.
[0041] In the present invention, the grinding balls used in the ball milling are preferably zirconia grinding balls.
[0042] In the present invention, the equipment for the first sintering and the second sintering in step (1) is preferably a tubular furnace.
[0043] In the present invention, the temperature of the first sintering in step (1) is preferably 400-500°C, more preferably 450-500°C, and more preferably 450°C; the time is preferably 3-6h, more preferably 4-5h, and more preferably 4h; the rate of heating to the temperature required for the first sintering is preferably 1.5-3°C / min, more preferably 2-3°C / min, and more preferably 2.5°C / min.
[0044] In the present invention, the temperature of the second sintering in step (1) is preferably 750-850°C, more preferably 780-850°C, and more preferably 800°C; the time is preferably 10-14h, more preferably 12-13h, and more preferably 12h; the rate of heating to the temperature required for the second sintering is preferably 1.5-3°C / min, more preferably 2-3°C / min, and more preferably 2.5°C / min.
[0045] In the present invention, the atmosphere of the first sintering and the second sintering in step (1) is preferably an oxygen atmosphere.
[0046] In the present invention, step (1) preferably includes cooling after the second sintering. The cooling conditions are not limited and can be any method known to those skilled in the art.
[0047] In the present invention, the method for removing the molten salt additive in step (1) is preferably washing.
[0048] In the present invention, the washing agent is preferably water. The number of washing times and the temperature of the water are not limited and can be adjusted according to needs.
[0049] In the present invention, the equipment for the tempering treatment in step (2) is preferably a tubular furnace.
[0050] In the present invention, the temperature of the tempering treatment in step (2) is preferably 700-750°C, more preferably 725-750°C, and more preferably 725°C; the time is preferably 4-6h, more preferably 5-6h, and more preferably 6h; the rate of heating to the temperature required for the tempering treatment is preferably 1.5-3°C / min, more preferably 2-3°C / min, and more preferably 2.5°C / min.
[0051] In the present invention, the atmosphere for the annealing treatment in step (2) is preferably an oxygen atmosphere.
[0052] In the present invention, the tempering treatment in step (2) preferably includes cooling. The cooling conditions are not limited and can be any method known to those skilled in the art.
[0053] The present invention also provides a molten salt-assisted valence gradient doping modified single crystal positive electrode material prepared by the preparation method.
[0054] The present invention also provides an application of the molten salt-assisted valence gradient doping-modified single crystal positive electrode material in a lithium-ion battery.
[0055] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.
[0056] In the present invention, the lithium ion battery is preferably a CR2025 button battery.
[0057] In the present invention, the lithium-ion battery preferably includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0058] In the present invention, the method for preparing the positive electrode sheet preferably comprises the following steps:
[0059] The molten salt-assisted valence gradient doped modified single crystal positive electrode material, conductive carbon black, a binder and an organic solvent are mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, dried, dried in a vacuum drying oven, and cut to obtain a positive electrode sheet.
[0060] In the present invention, the binder is preferably polyvinylidene fluoride (PVDF).
[0061] In the present invention, the organic solvent is preferably N-methylpyrrolidone (NMP).
[0062] In the present invention, the mass ratio of the molten salt assisted valence gradient doped modified single crystal positive electrode material, the conductive carbon black and the binder is not limited, and a solution familiar to those skilled in the art can be adopted. Specifically in the embodiment of the present invention, the mass ratio of the molten salt assisted valence gradient doped modified single crystal positive electrode material, the conductive carbon black and the binder is preferably 8:1:1.
[0063] In the present invention, the mixing method is preferably grinding. The grinding time is preferably 15 to 30 minutes, more preferably 20 to 30 minutes, and more preferably 25 minutes.
[0064] In the present invention, the drying temperature is preferably 80 to 120° C., more preferably 80 to 100° C., and more preferably 90° C.; the drying time is preferably 10 to 12 h, more preferably 11 to 12 h, and more preferably 12 h.
[0065] In the present invention, the negative electrode sheet is preferably a lithium sheet.
[0066] In the present invention, the separator is preferably a Celgard 2400 separator.
[0067] In the present invention, the electrolyte is preferably 1M LiPF6 DMC:EC=7:3wt%5%FEC.
[0068] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] This embodiment provides a method for preparing a molten salt-assisted magnesium-doped modified single crystal positive electrode material, comprising the following steps:
[0071] (1) MgO, LiOH·H2O, MnCO3 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 0.01:1.02:2:1.5, and zirconia grinding balls were used to mill the mixture in a planetary ball mill at 350 r / min and a ball-to-material ratio of 15:1 for 3 h; the ball-milled mixture was placed in a crucible, and an oxygen atmosphere was introduced into a tubular furnace, and the temperature was increased to 450°C at 2.5°C / min and kept at this temperature for 5 h, and then increased to 780°C at 2.5°C / min and kept at this temperature for 12 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a magnesium-doped modified single crystal positive electrode material precursor was obtained;
[0072] (2) The magnesium-doped modified single crystal cathode material precursor is placed in a tube furnace, an oxygen atmosphere is introduced, the temperature is increased to 725°C at a rate of 2.5°C / min, and the furnace is cooled to obtain a molten salt-assisted magnesium-doped modified single crystal cathode material, which is recorded as LMO-Mg.
[0073] Example 2
[0074] This embodiment provides a method for preparing a molten salt-assisted samarium-doped modified single crystal positive electrode material, comprising the following steps:
[0075] (1) Sm2O3, Li2CO3, Mn3O4 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 0.01:1.05:2:1.2, and the mixture was ball milled for 4 h in a planetary ball mill at 400 r / min and a ball-to-material ratio of 10:1 using zirconium oxide grinding balls; the ball-milled mixture was placed in a crucible, and an oxygen atmosphere was introduced into a tubular furnace, and the temperature was increased to 500°C at 2°C / min and kept for 4 h, and then increased to 800°C at 2°C / min and kept for 12 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a samarium-doped modified single crystal positive electrode material precursor was obtained;
[0076] (2) The samarium-doped modified single crystal cathode material precursor is placed in a tubular furnace, an oxygen atmosphere is introduced, the temperature is increased to 700°C at a rate of 2°C / min, and the furnace is cooled to obtain a molten salt-assisted samarium-doped modified single crystal cathode material, which is recorded as LMO-Sm.
[0077] Example 3
[0078] This embodiment provides a method for preparing a molten salt-assisted titanium-doped modified single crystal positive electrode material, comprising the following steps:
[0079] (1) TiO2, LiOH·H2O, MnO2 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 0.01:1.02:2:1.6, and zirconia grinding balls were used to mill the mixture in a planetary ball mill at 300 r / min and a ball-to-material ratio of 12:1 for 6 h; the ball-milled mixture was placed in a crucible, and an oxygen atmosphere was introduced into a tubular furnace, and the temperature was increased to 500°C at 2°C / min and kept for 5 h, and then increased to 850°C at 2°C / min and kept for 10 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a titanium-doped modified single crystal positive electrode material precursor was obtained;
[0080] (2) The titanium-doped modified single crystal cathode material precursor is placed in a tubular furnace, an oxygen atmosphere is introduced, the temperature is increased to 750°C at a rate of 2°C / min, and the mixture is annealed for 4 hours. The mixture is cooled in the furnace to obtain a molten salt-assisted titanium-doped modified single crystal cathode material, which is denoted as LMO-Ti.
[0081] Example 4
[0082] This embodiment provides a method for preparing a molten salt-assisted niobium-doped modified single crystal positive electrode material, comprising the following steps:
[0083] (1) Nb2O5, LiOH·H2O, Mn3O4 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 0.01:1.06:2:1.4, and zirconia grinding balls were used to mill the mixture in a planetary ball mill at 300 r / min and a ball-to-material ratio of 15:1 for 5 h; the milled mixture was placed in a crucible, oxygen atmosphere was introduced into a tubular furnace, the temperature was increased to 450°C at 3°C / min and kept for 6 h, and then the temperature was increased to 800°C at 3°C / min and kept for 13 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a niobium-doped modified single crystal positive electrode material precursor was obtained;
[0084] (2) The niobium-doped modified single crystal cathode material precursor is placed in a tube furnace, an oxygen atmosphere is introduced, the temperature is increased to 750°C at a rate of 3°C / min, and the furnace is cooled to obtain a molten salt-assisted niobium-doped modified single crystal cathode material, which is recorded as LMO-Nb.
[0085] Example 5
[0086] This embodiment provides a method for preparing a molten salt-assisted molybdenum-doped modified single crystal positive electrode material, comprising the following steps:
[0087] (1) MoO3, LiOH·H2O, MnCO3 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 0.01:1.05:2:1, and the mixture was ball milled for 4 h in a planetary ball mill at 400 r / min and a ball-to-material ratio of 10:1 using zirconium oxide grinding balls; the ball-milled mixture was placed in a crucible, and an oxygen atmosphere was introduced into a tubular furnace, and the temperature was increased to 450°C at 1.5°C / min and kept for 4 h, and then increased to 800°C at 1.5°C / min and kept for 12 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a molybdenum-doped modified single crystal positive electrode material precursor was obtained;
[0088] (2) The molybdenum-doped modified single crystal cathode material precursor is placed in a tubular furnace, an oxygen atmosphere is introduced, the temperature is increased to 725°C at a rate of 1.5°C / min, and the mixture is tempered for 5 hours. The mixture is cooled in the furnace to obtain a molten salt-assisted molybdenum-doped modified single crystal cathode material, which is recorded as LMO-Mo.
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing a single crystal positive electrode material, comprising the following steps:
[0091] (1) LiOH·H2O, MnCO3 and Li2SO4·H2O were placed in a ball mill according to a molar ratio of 1.08:2:2, and milled for 5 h in a planetary ball mill at 400 r / min and a ball-to-material ratio of 20:1 using zirconium oxide grinding balls; the ball-milled mixture was placed in a crucible, and an oxygen atmosphere was introduced into a tubular furnace, and the temperature was increased to 480°C at 3°C / min and kept for 4 h, and then increased to 780°C at 3°C / min and kept for 13 h, and then cooled with the furnace; the obtained product was washed in 50°C water for 5 times to remove the molten salt therein, and a single crystal positive electrode material precursor was obtained;
[0092] (2) The single crystal cathode material precursor is placed in a tube furnace, an oxygen atmosphere is introduced, the temperature is increased to 700°C at a rate of 3°C / min, and the furnace is cooled to obtain a single crystal cathode material, which is recorded as LMO.
[0093] The positive electrode materials obtained in Examples 1 to 5 and Comparative Example 1 were subjected to XRD testing. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the doped and modified lithium manganese oxide positive electrode material is the same as the lithium manganese oxide positive electrode material, without the generation of secondary phases and impurity peaks, and all diffraction peaks point to the spinel LiMn2O4 standard card (JCPDS 35-0782), belonging to the Fd3m space group, which is a standard lithium manganese oxide positive electrode material.
[0094] Application Examples 1 to 5, Comparative Application Example 1
[0095] (1) The positive electrode materials obtained in Examples 1 to 5 and Comparative Example 1, conductive carbon black (manufacturer Duoduo Chemical Reagent, model super C65) and PVDF (molecular weight 1 million) were mixed and ground at a mass ratio of 8:1:1 for 30 min, and NMP was added thereto and mixed to obtain a positive electrode slurry; the positive electrode slurry was uniformly coated on aluminum foil, and the loading amount was 4 mg·cm -2 , drying, drying in a vacuum drying oven at 80°C for 12h, cutting to obtain a positive electrode sheet;
[0096] (2) The positive electrode sheet, lithium sheet, Celgard 2400 separator, and 1M LiPF6DMC:EC=7:3wt%5%FEC electrolyte obtained in step (1) were assembled into CR2025 button-type batteries.
[0097] The assembled batteries of Application Examples 1 to 5 and Comparative Application Example 1 were placed in a blue power test system for cycle performance testing. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the doped and modified lithium manganese oxide positive electrode material has long cycle stability, which is much higher than the cycle retention rate of the undoped and modified lithium manganese oxide positive electrode material.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a molten salt-assisted valence gradient doping modified single crystal positive electrode material, characterized in that: The following steps are involved: (1) mixing a transition metal source, a lithium source, a manganese source and a molten salt additive, sequentially performing a first sintering and a second sintering, removing the molten salt additive, and obtaining a doped and modified single crystal positive electrode material precursor; (2) subjecting the doped modified single crystal positive electrode material precursor to a tempering treatment to obtain a molten salt assisted valence gradient doped modified single crystal positive electrode material; Wherein, the transition metal source in step (1) is Mg 2+ 、Sm 3+ 、Ti 4+ , Nb 5+ with Mo 6+ A transition metal oxide containing one or more doping elements.
2. The preparation method according to claim 1, characterized in that: In step (1), the lithium source includes LiOH·H2O or Li2CO3, the manganese source includes MnCO3, Mn3O4 or MnO2, and the molten salt additive is Li2SO4·H2O.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar ratio of the transition metal source, the lithium source, the manganese source and the molten salt additive is 0.01:1-1.08:2:1-2.
4. The preparation method according to claim 3, characterized in that: In step (1), the mixing method is ball milling; the ball milling time is 3 to 6 hours, the rotation speed is 300 to 400 r / min, and the ball-to-material ratio is 10 to 20:
1.
5. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the first sintering is 400-500° C., the time is 3-6 hours, and the rate of heating to the required temperature of the first sintering is 1.5-3° C. / min.
6. The preparation method according to claim 1 or 5, characterized in that: In step (1), the temperature of the second sintering is 750-850° C., the time is 10-14 hours, and the rate of heating to the temperature required for the second sintering is 1.5-3° C. / min.
7. The preparation method according to claim 6, characterized in that: In step (1), the atmosphere of the first sintering and the second sintering is an oxygen atmosphere.
8. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the tempering treatment is 700-750°C, the time is 4-6 hours, and the rate of heating to the temperature required for the tempering treatment is 1.5-3°C / min.
9. The molten salt-assisted valence gradient doping modified single crystal positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the molten salt-assisted valence gradient doping modified single crystal positive electrode material according to claim 9 in lithium ion batteries.
Citation Information
Cited By
Lithium-rich manganese-based positive electrode material with combined action of surface heterojunction and bulk phase doping as well as preparation method and application of lithium-rich manganese-based positive electrode material
CN120024944A
Preparation method and application of low-cost monocrystal lithium manganate positive electrode material
CN120505692A
A preparation method and application of low-cost single-crystal lithium manganese oxide positive electrode material
CN120505692B
